2012
DOI: 10.5688/ajpe76461
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Assessment of a Faculty Peer Observation and Evaluation Program

Abstract: Objective. To assess a previously described peer observation and evaluation program 2 years after implementation.Methods. An pre-implementation survey assessed faculty needs and attitudes related to peer evaluation. Two years after implementation, the survey was repeated and additional questions asked regarding adherence to peer observation and evaluation policies and procedures, feedback received, and impact on teaching. Results. Faculty attitudes towards peer evaluation stayed the same or improved post-imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 9 publications
1
51
0
Order By: Relevance
“…This culture has evolved over the past decade, with adoption of mandatory, formative, peer-faculty teaching assessments, 10 and faculty opinion leaders adopting various teaching strategies and demonstrating what is possible while acknowledging the shortfalls. [11][12][13][14] The finding that 26% of respondents tried more than 1 strategy also provided evidence of this continuous teaching quality improvement culture and the overall perceived value of the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This culture has evolved over the past decade, with adoption of mandatory, formative, peer-faculty teaching assessments, 10 and faculty opinion leaders adopting various teaching strategies and demonstrating what is possible while acknowledging the shortfalls. [11][12][13][14] The finding that 26% of respondents tried more than 1 strategy also provided evidence of this continuous teaching quality improvement culture and the overall perceived value of the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…41 Feedback from peers, however, serves as a powerful tool for formative assessment to enhance the quality of teaching. 42 Current research suggests that using multiple sources of feedback is more effective in evaluating teaching and professionalism. 43,44 Berk refers to this process as the "360 o multisource feedback model to evaluate teaching and professionalism."…”
Section: Formative Assessment Of Faculty Teachingmentioning
confidence: 99%
“…When a peer observation and evaluation program was established in one pharmacy school, over half of survey respondents agreed that results should be included as part yearly performance evaluations. 13 However, another pharmacy school reported that faculty members preferred that it be a formative process, as this A J P E A c c e p t e d D r a f t was deemed to be non-threatening. 22 Peer review as a summative assessment is desirable as it provides an alternative to student evaluations, which may be influenced by factors such as grade expectations.…”
Section: A J P Ementioning
confidence: 99%
“…12 Other pharmacy schools have reported higher percentages in the number of instructors who planned to make changes to their teaching practices after peer review compared to what we found in our study; contributing factors may have included a larger number of reviews conducted (resulting in more opportunity for feedback), training for observers, postobservation meetings, and a balance of positive and constructive feedback. 13 Nonetheless, positive confirmatory feedback may build confidence in instructors, and peer review of teaching provides a good opportunity for that since teaching is usually done in a solitary fashion. 12,19 Indeed we found that over half of our instructors indicated that the peer review process increased their confidence in their teaching strategies.…”
Section: A J P Ementioning
confidence: 99%
See 1 more Smart Citation